Evaluation of Digital Literacy to Educating Post-Millennials - Operio, Jennifer H. (International Journal of Research in STEM Education, 2022)
This paper is meant to evaluate the usefulness of digital literacy to learners who are classified as post-millennials. It strived to explore a possible retooling of education through innovative strategies to be able to increase value in classroom learning. Utilizing information and technology in communication to search, create, analyze and relay messages which requires cognitive and technical skills, is known as digital literacy. Post-millennials are those born from 1997 onwards. Since their generations are into the maximum use of the internet and technology in communication, the author deemed it necessary to evaluate the digital literacy of the post-millennials in a private school in one of the provinces in the Philippines. The respondents are the administrators, non-teaching staff, teaching staff, and students of this respondent school. The author utilized survey questionnaires to collect data from the participants. Results showed that less than half of the educators who participated favored digital teaching to students. However, this is not the case for learners because they all voted for digital learning. They mentioned that using digital tools is flexible, and they were more favorable in its integration into their classroom learning. The author, based on the findings, concluded that this present generation is more inclined to digital learning and teaching approaches. The author recommends that further and additional research is needed to determine more productive strategies for the provision of internet connection in schools and physical classrooms of the country.